2012
DOI: 10.4025/actasciagron.v34i2.12482
|View full text |Cite
|
Sign up to set email alerts
|

The influence of drying on the physiological quality of crambe fruits

Abstract: ABSTRACT. This study was performed to evaluate the physiological quality of Crambe abyssinica Hochst fruits subjected to drying under different treatments with air. The crambe fruits, with moisture content of 21.0 ± 1.3 (% w.b.), were manually collected and dried until their moisture content reached 7.0 ± 1.4 (% w.b.). The crambe fruits were dried with natural air (23°C mean temperature and 60.6% average relative humidity) and seven days after harvest in an experimental dryer with forced ventilation at tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 26 publications
2
5
1
11
Order By: Relevance
“…Also, a high percentage of normal seedlings in the first germination count and better germination synchronization were seen when crambe seeds were dried on hot air drying. Drying air temperature was approximately 55 °C and it did not immediately affect seed quality, agreeing with Costa et al (2012a) but contradicting results found by Costa et al (2012b), who reported that temperatures close to 60 °C is detrimental to the germination of crambe seeds. Zonta et al (2011) and Ullmann et al (2010) found no effect of drying temperatures respectively of 43 °C and 60 °C on the germination of Jatropha seeds.…”
Section: Resultscontrasting
confidence: 40%
See 1 more Smart Citation
“…Also, a high percentage of normal seedlings in the first germination count and better germination synchronization were seen when crambe seeds were dried on hot air drying. Drying air temperature was approximately 55 °C and it did not immediately affect seed quality, agreeing with Costa et al (2012a) but contradicting results found by Costa et al (2012b), who reported that temperatures close to 60 °C is detrimental to the germination of crambe seeds. Zonta et al (2011) and Ullmann et al (2010) found no effect of drying temperatures respectively of 43 °C and 60 °C on the germination of Jatropha seeds.…”
Section: Resultscontrasting
confidence: 40%
“…Costa et al (2012a) studied the effect of artificial drying with air at different temperatures on the physiological quality of crambe seeds and they did not observe effects on germination for the temperature used (35-90 °C). Costa et al (2012b), studying the same species but at drying with temperature from 23 to 70 °C, observed higher germination when the seeds were dried at 30 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Acredita-se, apesar da escassez de estudos que confirme esta hipótese, que o aumento da temperatura possa influenciar na quebra da dormência em sementes de crambe, conforme constatado em trabalho de Neves et al (2007), que verificaram ter a temperatura de 35 ºC melhor desempenho na germinação de sementes de crambe quando comparada à temperatura de 20 ºC. Contudo, para a temperatura de 70 ºC a germinação foi praticamente nula em todos os tratamentos, com exceção para as sementes com teores de água de 10% b.u., comportamento que corrobora os resultados obtidos com sementes de crambe submetidas à secagem na mesma temperatura por Costa et al (2012).…”
Section: Resultsunclassified
“…Este baixo percentual de germinação foi confirmado em trabalho conduzido por Ruas et al (2010), que obtiveram apenas 44% de viabilidade de sementes de crambe com pericarpo. Contudo, para o caso do crambe podese dizer que as informações sobre os procedimentos de secagem das sementes são recentes e abrangem os aspectos relacionados à cinética de secagem (COSTA et al, 2013;FARIA et al, 2012) e procedimentos de secagem (COSTA et al, 2012;MARTINS et al, 2012), até porque o cultivo da espécie somente agora começa a adquirir relevância nos trópicos. Assim, há necessidade da busca de informações sobre a temperatura ideal de secagem objetivando a produção de sementes com alto padrão de qualidade.…”
Section: Introductionunclassified
“…Assim pode-se inferir que o ambiente climatizado foi melhor para a quebra da dormência das sementes de crambe. Costa et al (2012), verificaram que a porcentagem média de sementes de crambe germinadas logo após à secagem nas temperaturas de 23, 30, 40, 50, 60 e 70 °C foi de 6,5; 17,1; 4,4; 7.1; 3,5 e 4,6% respectivamente, sendo que o aumento da temperatura interferiu negativamente na qualidade fisiológica das sementes. Estes pesquisadores também observaram os baixos valores da germinação e do IVG, indicando a dormência das sementes de crambe recém-colhidas.…”
Section: Resultsunclassified